Forensic accounting in organizations (2014)
The accounting system must cope with internal and external changes that will generate modifications in the accounting structure and therefore in public and private organizations, which are forced to restructure their processes to deal with these changes that are becoming more complex, at they are presented weaknesses that trigger potential fraud. Forensic accounting entables generating security and avoids fraudulent acts.